1992
DOI: 10.1002/mrd.1080320208
|View full text |Cite
|
Sign up to set email alerts
|

The role of TGF‐βs in mammalian development and neoplasia

Abstract: To date, three mammalian TGF-beta isoforms have been identified, each encoded by different genetic loci. Through each is very similar in primary amino acid structure, there are clear differences both in the mature bioactive peptide region and in the latency-associated peptide, which could potentially confer differential biological specificity. As one route to investigate differential biological function in vivo we have used gene specific probes for in situ hybridization studies to examine the distribution of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The pattern of distribution of AM-like immunoreactivity and its mRNA during murine development is very similar to that of other well established peptide growth factors. The distribution of AM immunoreactivity shown in our study is very similar to that reported for the TGF␤ isoforms 1, 2, and 3 in the E12-18.5 mouse embryos (2,27), suggesting that AM and the TGF␤s could be involved in analogous functions. AM distribution also shows some coincident locations with other active peptides such as PDGF, the fibroblast growth factors, insulin-like growth factors I and II, and the recently discovered cardiotropin, a member of the leukemia inhibitory factor/interleukin-6 family.…”
Section: Discussionsupporting
confidence: 88%
“…The pattern of distribution of AM-like immunoreactivity and its mRNA during murine development is very similar to that of other well established peptide growth factors. The distribution of AM immunoreactivity shown in our study is very similar to that reported for the TGF␤ isoforms 1, 2, and 3 in the E12-18.5 mouse embryos (2,27), suggesting that AM and the TGF␤s could be involved in analogous functions. AM distribution also shows some coincident locations with other active peptides such as PDGF, the fibroblast growth factors, insulin-like growth factors I and II, and the recently discovered cardiotropin, a member of the leukemia inhibitory factor/interleukin-6 family.…”
Section: Discussionsupporting
confidence: 88%
“…The embryonic heart will start to pulsate at day 8.5-9 pc [Rugh, 19681, so that the formation of beating muscle in aggregates follows similar kinetics. We have obtained evidence that both TGF-p2 protein and mRNA are present in the embryonic heart and associated regions at day 8-8.5 pc [Akhurst et al, 1992;Dickson et al, 19931. Cardiac myocytes but not endocardium or cushion cells stain intensively with a polyclonal antibody specific for TGF-fi2.…”
Section: Discussion Embryonic Stem Cells and Tgf-pmentioning
confidence: 96%
“…conservation of function between these two organisms (Akhurst et al, 1992;Gatherer et al, 1990). Moreover, the finding of vascular dysplasia and malformation resulting from germ-line loss of TGF␤ signaling components in the hereditary hemorrhagic telangiectasias (HHTs) (Berg et al, 1997;McAllister et al, 1994), familial thoracic aortic aneurysms and dissections (FTAAD) (Pannu et al, 2005) and other cardiovascular malformations (Loeys et al, 2005;Mizuguchi et al, 2004), emphasizes the importance of TGF␤ signaling in vascular remodeling and homeostasis in humans (Akhurst, 2004).…”
Section: Introductionmentioning
confidence: 99%